Gubera . Junking - Lehel, Oláh (Hungary, 2003)
Duration: 00:20:00 Lehel Oláh’s documentary is an experiment balancing on the border of several genres. Moments recorded – with brilliant camera work – in different periods of the year tell us a lot about the life of a big city. The authors collect “junk-images” in Budapest during junking developed into a lyric “socio road movie” in order to let other people use them.